REGIOCULTURAL BRANDING AS A STRATEGIC TRANSFORMATION: BRIDGING MARKET ORIENTATION, CULTURAL INTELLIGENCE, AND MARKETING PERFORMANCE IN BATIK SMES - Rois, Tatang; Fitriani, Lili; Wachjuni, Wachjuni (Faculty of Economic and Business, University of Pasundan, 2026)
Previous studies examining the relationship between market orientation and marketing performance have reported inconsistent findings. Batik small and medium enterprises (SMEs) in Indonesia continue to face challenges in improving their marketing performance. This study examines the role of regiocultural branding as a mediating mechanism linking market orientation and marketing performance, while also considering the influence of cultural intelligence. A survey was conducted among 200 owners or managers of batik SMEs in Cirebon Regency, Indonesia, selected using random sampling. Data were analyzed using Structural Equation Modeling (SEM) with AMOS. The results indicate that market orientation and cultural intelligence significantly strengthen regiocultural branding, which in turn positively affects marketing performance. Furthermore, regiocultural branding is confirmed to mediate the relationship between market orientation and marketing performance. These findings highlight the importance of integrating local cultural identity into branding strategies to enhance the competitiveness of batik SMEs.